Hubungan Suhu Dan Kelembaban Rumah dengan Kejadian Penyakit ISPA Pada Balita di Wilayah Kelurahan Panembahan Yogyakarta Tahun 2011 - Andri Setiawan; F.X. Amanto Rahardjo; Siti Hani Istiqomah (Poltekkes Kemenkes Yogyakarta, 2011)
Acute Respiratory Infection (ARI) is one of major health problems in Indonesia because of its high number of incidence. Under five children are the most vulnerable age groups to ARI. It is estimated that children in average will experience 3-6 events of ARI every year. Unhealthy housing conditions such as unadequate temperature and humidity of bedrooms may affect ARI incidence. The purpose of this research is to determine whether temperature and humidity play as risk factors for ARI among under five children in Panembahan Village of Yogyakarta City, by conducting a case control study Samples were determined based on diagnostic results in Puskesmas Kraton medical record. As the case group was children who were diagnosed with ARI and those who were not was belong to the control group. To measure the physical condition in children’ bedroms, the instruments used were digital thermohygrometer, rollmeter, and questionnaire. Results of the study showed that the OR for temperature was 1,818 (95% CI=0,518 – 6,382; p value 0,347) and for humidity was 4,030 (95% CI=1,372 – 11,839; p value=0,010). It is advised for residents in Panembahan Village to keep the temperature and humidity inside their house fulfilling the requirement by regularly open the windows every morning and afternoon for allowing good air circulation.